Strengthening primary care through patient registration: a review of 10 countries. (30th September 2020) - Marchildon, G; Allin, S; Quentin, W
Abstract: Background: Effective primary care requires continuity in the patient-provider relationship so that the primary care provider can act as the central coordinator of services. For this reason, some high-income countries have insisted on patient registration with a primary care team as part of different reform efforts. This paper develops a framework for analysing the characteristics of patient registration across countries; applies this framework to a selection of high-income countries that have introduced registration; and identifies challenges related to registration and ongoing reform efforts. Methods: Based on a literature review, 10 countries - Canada, Denmark, England, France, Germany, Israel, Norway, Sweden Switzerland, and the Netherlands - were selected for analysis. Information was collected using a standardized questionnaire completed by national researchers who reviewed relevant literature and policy documents to report on the establishment and evolution of the policy, the requirements for providers and patients, the benefits for patients, providers and payers, and its connection to primary care reform. Results: Patient registration establishes a triangular accountability relationship between patients, providers and payers that many reform advocates claim is the key to achieving better continuity and coordination of care. Results will provide information about the introduction of patient registration in the included countries; the characteristics of patient registration agreements; quantitative indicators, such as the proportion of patients registered, the proportion of primary care providers registering patients, and the average list size of providers. Recent reform experiences and ongoing challenges will also be reviewed. Conclusions: This study will allow us to assess patient registration in terms of its key characteristics and outcomes. A preliminary evaluation of the policy's strengths and weaknesses based on key reform criteria is also presented.